Pengaruh Kompetensi Sumber Daya Manusia, Whistleblowing dan Good Corporate Governance Terhadap Pencegahan Kecurangan Akuntansi Pada BUMDes Se- Kecamatan Bebandem - Witari, Ni Putu Cesaria; Sumadi, Ni Komang; Ayu, Putu Cita (Hita Akuntansi dan Keuangan, 2025)
ABSTRACT BUMDes, a business unit focused on saving loans and utilizing village funds for asset management and services, aims to improve the prosperity of the community. However, many BUMDes face challenges due to corruption. One solution to reduce fraud is enhancing human resources (HR) competence. This study uses double linear analysis with data collected through a five-point Likert scale. The data analysis includes narrative statistics, instrumental tests, classical predictive tests, double linear regression, and hypothesis testing. The results show that HR competence has a positive and significant effect on fraud prevention in BUMDes in Bebandem, meaning that improving HR skills can reduce fraud. In contrast, whistleblowing does not significantly impact fraud prevention, possibly due to system weaknesses or ineffective whistleblowing systems. Good corporate governance (GCG), however, also has a positive and significant effect on fraud prevention. These findings highlight the importance of HR competence and GCG in preventing fraud in BUMDes, while improving whistleblowing systems is needed for better effectiveness.